Jund orchestrates cis -regulatory element dynamics to facilitate endothelial-to-hematopoietic transition - Jiani Guo; Mengyao Liu; Feng Liu; Lu Wang (Proceedings of the National Academy of Sciences, 2025)
The tightly controlled spatiotemporal expression of developmental genes depends on the concerted action of cis -regulatory elements (CREs) and transcription factors (TFs) to ensure cell fate decisions. Endothelial-to-hematopoietic transition (EHT) is a cell fate transition process by which endothelial cells acquire hematopoietic identity and become hemogenic endothelial cells (HECs) and then hematopoietic stem and progenitor cells, but the underlying CRE network dynamics and its regulation by TFs remain unclear. In this study, we characterized the dynamics of CRE activation and TF occupancy during zebrafish EHT, and found that the enhancer–promoter collaboration forms the basis for EHT. Moreover, a ubiquitously expressed TF AP-1 collaborates with diverse lineage-specific TFs to remodel enhancer landscape. Deletion of AP-1 family member Jund impaired hematopoietic specification, resulting from the enhanced endothelial identity in the HEC. Mechanistically, Jund and hematopoietic TF Hoxa9a collectively repress the activity of an endothelial-related dll4 enhancer through tight control of the active histone modification H3K27ac. Our study provides insights into the cooperative function among ubiquitous TFs and cell type–specific TFs in orchestrating cell fate transition.